Hyperpolarizability of donor–acceptor azines subject to push–pull character and steric hindrance - Kleinpeter, Erich; Stamboliyska, Bistra A. (Tetrahedron, 2009)
The push–pull character of two series of donor–acceptor azines has been quantified by 13C, 15N chemical shift differences of the partial C(1) N(1) and N(2) C(2) double bonds in the central linking C(1) N(1)–N(2) C(2) unit and by the quotient of the occupations of the bonding π and anti-bonding π ∗ orbitals of these bonds. Excellent correlation of the latter push–pull parameter with the corresponding bond lengths d C N strongly recommend both the occupation quotients π ∗/π and the corresponding bond lengths as reasonable sensors for quantifying the push, pull character along the C N–N C linking unit, for the donor–acceptor quality of the two series of azines and for the molecular hyperpolarizability ß 0 of these compounds. Within this context, reasonable conclusions concerning the interplay of steric hindrance in the chromophore, push–pull character and hyperpolarizability of the azines and their application as NLO materials will be drawn. [Display omitted]